Tracer Study of Architectural Drafting: An Inputs for the Integration of Enhanced Learning Competencies in Faculty Development Program - Flores, Cariza; Daran, Danilo N.; Aquino, John Michael D. (Jayapangus Press, 2024)
This study aims to explore the profile of graduates in the field of architectural drafting, their learning capabilities, skills, and knowledge, and their readiness towards the workforce. The results will be the inputs to integrate the enhanced learning competencies to faculty development program. This study used a quantitative research design and random sampling technique to select the target graduates of the architectural drafting program from AY 2016-2020 which composed of 105 graduates based on the list given by the registrar’s office. The data for this study collected through a survey questionnaire which was modified based on the Graduate Tracer Research Questionnaire from CHED. The results revealed that most of the respondents are single, male and most of them work in contract and regular roles, and many of them feel their jobs are connected to their academic program. Competitive salary and benefits, chances to use specialized skills, and the possibility of professional growth are the main reasons why recent graduates decide to remain in their current job. Moreover, graduates show a good grasp of industry concepts that are pertinent to architectural drafting and strong analytical thinking, problem-solving, and communication skills. Proficiency in fundamental drafting skills, CAD software usage, technical drawing standards, and professional ethics are demonstrated by graduates. Furthermore, with the knowledge and skills needed to thrive in the field of architectural drafting, graduates are well-prepared for the workforce. They exhibit a readiness to work with professionals in the field.